ADULT PATIENT WITH BRONCHOGENIC CYST - A RARE PULMONARY DEVELOPMENTAL ANOMALY - Pejkovska, Sava; Karkinski, Dimitar; Angelovska, Irina; Jovanoski, Smilko; Debreshlioska, Angela; Miletic , Milena; Grueva-Karanfilova, Ada; Ismaili, Irfan; Bojadzieva Stojanoska, Biljana; Krstic Nakovska, Olivera; Dimoska, Gabrijela; Dokikj, Dejan (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2022)
Bronchogenic cysts are anomalies in the prenatal development of the lungs that we encounter extremely rarely in the adult population because they are diagnosed in childhood, usually after birth. So far, there is no published case in the Republic of Macedonia with a diagnosed bronchogenic cyst in the lung parenchyma. Such cases need to be solved with surgical intervention in order to avoid possible complications.
ВОЗРАСЕН ПАЦИЕНТ СО БРОНХОГЕНА ЦИСТА - РЕТКА АНОМАЛИЈА ВО РАЗВОЈОТ НА БЕЛИТЕ ДРОБОВИ
Keywords: bronchogenic cyst; adults; parenchymal; mediastinal